Energy storage of supercapacitor electrodes on carbon cloth enhanced by graphene oxide aerogel reducing conditions. (December 2020) - Okhay, Olena; Tkach, Alexander; Gallo, Maria J. Hortiguela; Otero-Irurueta, Gonzalo; Mikhalev, Sergey; Staiti, Pietro; Lufrano, Francesco
Highlights: flexible textile electrodes from rGO-aerogels/CNT-composite were developed. high rate capability of rGO+CNT+PVDF-HFP electrodes. composite with 180°C-rGO-aerogel on carbon cloth has useful specific capacitance. Abstract: Supercapacitor performance can be enhanced when the specific capacitance of its electrodes is increased by the electrode fabrication parameters, composition, and structure. The electrode application range can be enlarged from supercapacitors to tribo- or piezo- generators as a part of self-charging power cell for one-step energy conversion and storage by the use of flexible kind of support for the active material such as conducting textile. Here, we use suspended mixture of graphene oxide (GO) aerogel, carbon nanotubes and poly(vinylidene fluoride-co-hexafluoropropylene) for screen printing of flexible electrodes on carbon cloth. Two kinds of reduced graphene oxide (rGO) aerogels are prepared using freeze drying of GO solution with further reduction at 180 °C in vacuum and at 700 °C in Ar, respectively. The composite electrodes with rGO annealed at 180 °C show higher specific capacitance likely because of better homogeneity and surface wettability and despite lower reduction degree and electrical conductivity compared to that of the electrodes with rGO heat treated at 700 °C. The highest specific capacitance values of 129, 116, 110, 104 F g − 1 at 0.1, 0.2, 0.5 and 1 A g − 1, respectively, are obtained for the flexible composite electrode on the carbon cloth with rGO aerogel annealed at 180 °C. Moreover, the rGO-aerogel-based electrode shows high rate capability because it can retain 80% of capacitance as the discharge current is raised from 0.1 to 1 A g − 1 . This stable capacitive performance of the prepared flexible electrodes demonstrates their high potential for wearable electronics and self-powered devices. Graphical abstract: Image, graphical abstract